PUBLIC KNOWLEDGE, PERCEPTION, AND ATTITUDES TOWARDS BIOFUEL ENERGY TECHNOLOGIES IN LAGOS, NIGERIA - Emmanuel, Abdul-Azeez (My University, 2014)
This research aims to investigate the level of awareness and prevailing attitudes of the Lagos public towards renewable energy, with special focus on biofuel energy. Nigeria as a country is heavily reliant on fossil fuels despite having high RE (renewable energy) resources. The importance of this study stems from the need to better understand the role of education in cultivating awareness of RE, which is necessary for the public (especially the young population) to become responsible energy consumers. Additionally, this thesis aims to highlight the importance of implementing energy education as early as possible to encourage biofuel acceptance, which is necessary to alleviate the risk from fossil fuel-related environmental problems. To answer the research questions, a combination of multiple choice and dichotomous web-based questionnaire was designed to ascertain the public’s awareness, attitude, and willingness to invest in biofuel energy technologies. In total, 134 respondents completed the survey. The results show that about 75% have are aware of biofuel energy. While a further 65% are willing to use the technology when it becomes available and an even greater number of respondents are willing to pay extra for their household to have biofuel energy. In general, this indicates a positive attitude towards new energy technology acceptance and use.
Keywords: Biofuel; Public acceptance; Lagos; Renewable energy; awareness; power; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|